Functional activation during reading in relation to the sulci of the angular gyrus region. Issue 5 (17th June 2013) - Segal, Emily; Petrides, Michael
Abstract Neurological studies suggest that the angular gyrus region of the inferior parietal lobule may be critical for reading. However, unambiguous demonstration of angular gyrus involvement from lesion and functional neuroimaging studies is lacking, partly because of the absence of detailed morphological descriptions of this region. On the basis of our recent anatomical examination of this region and a tightly controlled functional magnetic resonance imaging paradigm, the present investigation demonstrated reading‐related activity in the region of the angular gyrus that lies between the central and posterior branches of the caudal superior temporal sulcus, namely cytoarchitectonic area PG. Analysis of functional connectivity showed increased functional coupling during reading of area PG with the language areas of Broca and Wernicke, and a region previously identified as the visual word form area. Thus, the parietal reading area has been precisely localized, and its interactions with other cortical areas during reading have been demonstrated.